2022
DOI: 10.1523/jneurosci.2102-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Neurons in the Dorsomedial Hypothalamus Promote, Prolong, and Deepen Torpor in the Mouse

Abstract: Torpor is a naturally occurring, hypometabolic, hypothermic state engaged by a wide range of animals in response to imbalance between the supply and demand for nutrients. Recent work has identified some of the key neuronal populations involved in daily torpor induction in mice, in particular, projections from the preoptic area of the hypothalamus to the dorsomedial hypothalamus (DMH). The DMH plays a role in thermoregulation, control of energy expenditure, and circadian rhythms, making it well positioned to co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 38 publications
3
5
0
Order By: Relevance
“…2c ). These effect sizes were similar to the previously reported fasting-induced torpor in mice 11 , 24 . Ultrasound suppressed oxygen consumption before the fall in body temperature (Extended Data Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…2c ). These effect sizes were similar to the previously reported fasting-induced torpor in mice 11 , 24 . Ultrasound suppressed oxygen consumption before the fall in body temperature (Extended Data Fig.…”
Section: Resultssupporting
confidence: 91%
“…Ultrasound stimulation systemically suppressed metabolism and thermogenesis, switched energy substrate utilization to fat and decreased heart rate, which collectively are key features of natural torpor 11 , 23 . Single ultrasound stimulation was found to induce a hypothermic and hypometabolic state lasting up to approximately 1 h, which is consistent with natural torpor 24 , 25 . This prolonged duration was also consistent with a previous report that found optogenetic activation of QRFP neurons in the POA resulted in a state of hypothermia lasting for longer than 30 min following a 1-s light illumination 12 .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…We confirmed that female mice also showed a similar sufficient and persistent hypothermia using the same method ( Figure 1 E) because sex differences exist in fasting-induced daily torpor and that the duration of torpor is longer in female mice. 33 , 34 The optogenetic induction of QIH may help identify the physiological changes in the recovery/arousal phase of hibernation and the mechanisms underlying sex differences.…”
Section: Resultsmentioning
confidence: 99%
“…Only recently the neural pathways that control torpor are being unraveled 15 17 . Moreover, it could also provide a much-needed method to improve the radiation resistance of space crews 18 .…”
Section: Introductionmentioning
confidence: 99%